2003
DOI: 10.1159/000069008
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cytokine Levels, Cigarette Smoking and Airway Responsiveness among Pregnant Women

Abstract: Background: Five to twenty percent of healthy, nonasthmatic individuals exhibit airway hyperreactivity. Because cytokines are important intermediates in airway responses, we investigated the relationship between serum cytokines and airway responsiveness in a well-characterized population of pregnant women. Methods: We analyzed serum levels of interleukin-4 (IL-4), IL-5, IL-6, interferon-γ (IFN-γ), and granulocyte-macrophage colony-stimulating factor (GM-CSF) in frozen sera from 240 pregnant nonasthmatic subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Kauffmann et al [65] found a positive relation in man between BHR and haptoglobin levels, and Tusoda et al [74] recently reported a positive association in pregnant women between BHR and some cytokines -including IL-6 and granulocytemacrophage colony stimulating factor. Recently, the Buyukozturk et al [75] study demonstrated that acute phase reactant serum amyloid A is raised in patients with asthma, which may indicate the presence of systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Kauffmann et al [65] found a positive relation in man between BHR and haptoglobin levels, and Tusoda et al [74] recently reported a positive association in pregnant women between BHR and some cytokines -including IL-6 and granulocytemacrophage colony stimulating factor. Recently, the Buyukozturk et al [75] study demonstrated that acute phase reactant serum amyloid A is raised in patients with asthma, which may indicate the presence of systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Lower levels of these cytokines among smokers vs. non-smokers were observed in all four sub-studies (NYUWHS-OVCA, NYUWHS-NHL, ORDET, and NSHDS). Previous studies on current smoking and cytokines among healthy individuals have found positive [34, 4450], inverse [51, 52], and null [49, 5255] associations. Inconsistent findings may be a result of incomplete control for lifetime exposure to cigarette smoke (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although, there are former studies showing that there is an effect of not only infection but also of some other environmental factors on the cytokine spectrum of the cord blood, e.g. maternal smoking or air pollution [25].…”
Section: Discussionmentioning
confidence: 99%